2001
DOI: 10.1037/0096-1523.27.4.942
|View full text |Cite
|
Sign up to set email alerts
|

Infant sensitivity to trajectory forms.

Abstract: The authors investigated whether infants are sensitive to visual event trajectory forms, and whether they are sensitive to the underlying dynamics of trajectory forms. The authors habituated 8-month-old infants to a videotaped event run either forward or reversed in time and then switched them to the same event run in the opposite direction. Infants dishabituated when switched to the event with the novel direction in time, indicating sensitivity to the form of the trajectory. Infants exhibited equivalent habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It will be helpful to think of this as the negativeentropy condition. Other studies Gibson & Kaushall, 1973;Pittenger, 1990;Wickelgren & Bingham, 2001) on event dynamics, time-reversed motions, and animate versus inanimate dynamics have shown similar sensitivity to negative-entropy motion. There was no statistically significant sensitivity to normal but relatively inelastic bounces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be helpful to think of this as the negativeentropy condition. Other studies Gibson & Kaushall, 1973;Pittenger, 1990;Wickelgren & Bingham, 2001) on event dynamics, time-reversed motions, and animate versus inanimate dynamics have shown similar sensitivity to negative-entropy motion. There was no statistically significant sensitivity to normal but relatively inelastic bounces.…”
Section: Discussionmentioning
confidence: 99%
“…Bingham, Schmidt, and Rosenblum (1995) found that observers could distinguish real bounces from hand-driven bounces with the same period, suggesting, again, that the trajectory form is the source of information. Finally, Muchisky and Bingham (2002) found that observers are indeed sensitive to such variations in trajectory forms (see also Wickelgren & Bingham, 2001). …”
Section: Overviewmentioning
confidence: 99%
“…Muchisky and Bingham found that adults could discriminate between the events up to small differences in form, showing that adults are sensitive to variations in the shapes of speed profiles. Wickelgren and Bingham (2001) have also shown that infants as young as 8 months are sensitive to trajectory forms.…”
mentioning
confidence: 99%
“…The origin of a given phase plane is defined by the location and value of peak speed, and this origin defines the frame of reference required to identify the phase of a movement of given amplitude and frequency. Perceptually, phase is a location along the trajectory form (Muchisky & Bingham, 2002;Wickelgren & Bingham, 2001). This location is specified in the phase-driven model by the current relative proportion of the peak speed.…”
mentioning
confidence: 99%